Performance evaluation of two-layer active magnetic regenerators with second-order magnetocaloric materials. (5th August 2016) - Teyber, R.; Trevizoli, P.V.; Christiaanse, T.V.; Govindappa, P.; Niknia, I.; Rowe, A.
Highlights: Four two-layer regenerators compositions are experimentally evaluated. Interface temperature measurements allow analysis of individual layers. Optimal transition temperature spacing is identified for tested parameters. Experiments are compared with modeling predictions. Abstract: Magnetic heat pumps and cooling systems typically use a magnetocaloric material in an active magnetic regenerator (AMR) cycle for application near room temperature. One method of improving AMR performance is to layer regenerators with spatially varying Curie (or transition) temperatures. To study the impact of layering on AMR performance, four regenerator compositions comprised of two-layers are experimentally tested with interface temperature measurements. Each regenerator uses Gd as the layer with the highest Curie temperature; the second layer uses Gd and three compositions of Gd1− x Y x . The four regenerators are the same size and are tested using three different rejection temperatures and displaced volumes. Numerical simulations are in good agreement with the experimental results. The two-layer regenerators present the largest performance improvements for the no-load conditions and, in general, develop the peak exergetic cooling power for almost all operating conditions.